2009
DOI: 10.3899/jrheum.090030
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodulosis and Aseptic Granulomatous Lung Disease Occurring in Patients with Rheumatoid Arthritis Receiving Tumor Necrosis Factor-α-Blocking Agent: A Case Series

Abstract: Aseptic pulmonary nodular inflammation corresponding to rheumatoid nodules or noncaseating granulomatous inflammation can occur during anti-TNF-alpha therapy for RA, mainly etanercept. The mechanism explaining such a reaction is not clear but certainly includes different processes. These cases of pulmonary nodular inflammation generally have a benign course and do not systematically require withdrawal of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…In some cases, the histology is typical of a rheumatoid nodule while in others, aseptic necrotizing granulomas have been documented in biopsy. These lesions have been mostly associated with etanercept [9]. One of us has cared for a child with JIA who developed pancytopenia while on etanercept and exhibited noncaseating aseptic granuloma on bone marrow biopsy (unpublished observation).…”
Section: Drugsmentioning
confidence: 94%
“…In some cases, the histology is typical of a rheumatoid nodule while in others, aseptic necrotizing granulomas have been documented in biopsy. These lesions have been mostly associated with etanercept [9]. One of us has cared for a child with JIA who developed pancytopenia while on etanercept and exhibited noncaseating aseptic granuloma on bone marrow biopsy (unpublished observation).…”
Section: Drugsmentioning
confidence: 94%
“…29 A study of 5 cases highlights the unpredictable nature of pulmonary rheumatoid nodules, which can evolve, regress, or remain unchanged despite lack of any therapeutic changes. 28 They do not seem to trend with clinical disease course, as has been noted with subcutaneous nodules, and can worsen after initiation of anti-TNF therapy 30 (see section Accelerated Nodulosis).…”
Section: Systemic Location Of Rheumatoid Nodulesmentioning
confidence: 94%
“…62 The increased rheumatoid nodule formation during infliximab therapy noted in this study coincides with numerous reports of onset or worsening pulmonary rheumatoid nodules after initiation of anti-TNF therapy. 30 Holding TNF inhibitor therapy resulted in a 30% reduction in pulmonary nodules. 63 In contrast to TNF inhibitors, B-cell depletion with rituximab has shown potential benefits.…”
Section: Treatment Of Rheumatoid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports indicated that MTX and LEF may have the disadvantage of tending to make the nodules worse [4,7,11]. Tumor necrosis factor (INF) inhibitors do not have sustained or reliable effects on nodules in some reports [4,12,13] versus improvement reported by others [14]. The same may apply on B-cell depletion.…”
Section: Discussionmentioning
confidence: 99%